Численные оценки электродинамических процессов в индукторной системе с притягивающим экраном и плоским прямоугольным соленоидом - Чаплыгин, Е.А.; Барбашова, М.В.; Коваль, А.Ю. (Електротехніка і електромеханіка, 2018)
Проведены численные оценки и анализ полученных результатов для токов и сил в исследуемой индукторной системе
с притягивающим экраном и прямоугольным соленоидом. Выявлено, что при уменьшении глубины вмятины в металле, амплитуда, возбуждаемых электродинамических усилий, растёт. Анализ показал, что значение сил отталкивания, интегральное во времени, ниже развиваемых сил притяжения. При достаточно низких рабочих частотах действующих полей, рассмотренная система работает, как инструмент магнитно-импульсного притяжения тонкостенных листовых металлов. Проведено чисельні оцінки та аналіз отриманих результатів для струмів і сил в досліджуваній індукторній системі з
притягуючим екраном і прямокутним соленоїдом. Виявлено, що при зменшенні глибини вм'ятини в металі, амплітуда, збуджуваних електродинамічних зусиль, зростає. Аналіз показав, що значення сил відштовхування, інтегральне в
часі, нижче сил притягання, що розвиваються. При досить низьких робочих частотах діючих полів, розглянута система працює, як інструмент магнітно-імпульсного притягання тонкостінних листових металів. Purpose. To carry out numerical estimates of currents and forces
in the investigated inductor system with an attractive screen (ISAS)
and determine the effectiveness of the force attraction. Methodology. The calculated relationships and graphical constructions were
obtained using the initial data of the system: induced current in the
screen and sheet metal; the distributed force of attraction (Ampère
force); the repulsive force acting on the sheet metal (Lorentz
force); amplitude values of the force of attraction and repulsion;
phase dependence of the force of attraction, the repulsive force and
the total resulting force. Results. The results of calculations in the
form of graphical dependencies of electrodynamic processes in the
region under the conductors of a rectangular solenoid of inductor
system with an attracting screen are presented. The graphs of
forces and currents in region of dent are obtained. In the paper the
analysis of electrodynamics processes for whole area under the
winding of inductor system with an attractive screen is shown. The
flowing this processes in the region of dent a given geometry is
presented. Originality. The considered inductor system with an
attractive screen and a rectangular solenoid is improved, in comparison with the previous developed ISAS. It has a working area
under the lines of parallel conductors in the cross section of a rectangular solenoid, and this allows to place a predetermined portion of the sheet metal anywhere within the working region. Comparison of the indicators of electrodynamics processes in the considered variants of calculation shows an approximate growth of
almost 1.5 times the power indicators in the area of the accepted
dent in comparison with similar values for the entire area under
the winding of the ISAS. Practical value. The results obtained are
important for the practice of real estimates of the excited forces of
attraction. With a decrease in the dent, the amplitude of the electrodynamics forces being excited is growing proportionally (for
example, when the depth decreases by 3 mm, the forces increase
more than 2 times). The highest efficiency of force attraction is for
sheet metal regions, the dimensions do not exceed the transverse
dimensions of the winding branches of the exciting solenoid.